The pleasure garden - Bate, Stanley 1911-1959 (British Film Institute, 2009)
"People quietly or campily pass the time in an overgrown garden full of statues, while a puritanical, funereal gentleman posts bills prohibiting all leisure activities." [imdb.com]
Titelzusatz von DVD-Hülle: "a film by James Broughton"
Original: Großbritannien 1953
Special features: "The Phoenix Tower" (1957, 39 mins), a short documentary charting the construction of the BBC's Crystal Palace Television Tower ; fully illustrated booklet with film notes, an original review and a history of the Crystal Palace ; fully uncompressed PCM mono audio
Bildformat 1.33:1
Keywords: Film; DVD-Video